Asymmetric Lattice Disorder Induced at Oxide Interfaces. Issue 8 (20th February 2020) - Spurgeon, Steven R.; Kaspar, Tiffany C.; Shutthanandan, Vaithiyalingam; Gigax, Jonathan; Shao, Lin; Sassi, Michel
Abstract: Control of order–disorder phase transitions is a fundamental materials science challenge, underpinning the development of energy storage technologies such as solid oxide fuel cells and batteries, ultra‐high temperature ceramics, and durable nuclear waste forms. At present, the development of promising complex oxides for these applications is hindered by a poor understanding of how interfaces affect lattice disordering processes and defect transport. Here, the evolution of local disorder in ion‐irradiated La2 Ti2 O7 /SrTiO3 thin film heterostructures is explored using a combination of high‐resolution scanning transmission electron microscopy, position‐averaged convergent beam electron diffraction, electron energy loss spectroscopy, and ab initio simulations. Highly non‐uniform lattice disordering driven by asymmetric oxygen vacancy formation across the interface is observed. Theory calculations indicate that this asymmetry results from differences in the polyhedral connectivity and vacancy formation energies of the two interface components, suggesting ways to manipulate lattice disorder in functional oxide heterostructures. Abstract : Correlative atomic‐scale imaging and theory calculations reveal the presence of asymmetric oxygen vacancy formation during disordering of complex oxide interfaces.